Measurements of Film Thickness and Pressure Distribution for Optimized Thrust Air Bearing - Mohd Danial, Bin Ibrahim; Sunami, Yuta; Ochiai, Masayuki; Hashimoto, Hiromu (2010)
In this paper, we describe the film thickness and pressure measurement of the optimized thrust air bearing. In our recent study, a new optimization technique of the bearing groove geometry of the hydrodynamic thrust air bearings was proposed and a new groove geometry having a bending curve in outer vicinity of the bearing surface was obtained. Furthermore, in this study, the drastic improvement of the bearing dynamic stiffness was verified by the dynamic characteristic experiment using the original high-speed bearing test rig. However the relative error of the film thickness between the theory and experiment is large compared with that of dynamic stiffness. Consequently, it has been considered that the improvement of the measurement accuracy for film thickness is one of the most important problems. On the other hand, the generation of the negative pressure on the optimized bearing surface has not been confirmed experimentally, and it is also important to verify the negative pressure generation by measurement. Therefore, in this study, we examined the improvement of the measurement accuracy of the film thickness and the pressure measurement of the optimized bearing. As a result, the accuracy of air film thickness is drastically improved applying a newly proposed compensation method and the negative pressure on the optimized bearing can be found experimentally.